The third sector in the planning, production, and regeneration of inclusive public space : Notes from an ongoing experience in a distressed Sicilian neighborhood - Privitera, Elisa (AESOP, 2020)
Due to the decrease of public and private funds invested in the production and regeneration of public spaces in Southern Italy, collaborative efforts among public/private actors seems to be a compelling alternative strategy for supporting urban transformations. While both planning and policy approaches have been unable to completely adapt to meet these growing demands, many actors, such as the third sector, within distressed neighborhoods and communities, act as place-makers and seem to be the last stronghold of resistance for exercising the right to the city. What can be done to overcome the classical rhetoric on the informal/formal dichotomy in the urban transformations and to reinforce the efforts of creating inclusive and enabling public spaces in new experimental ways? This paper proposes a reflection on this current dilemma through the presentation of ongoing re-appropriation and self-recovery practices over the last four years in San Berillo, a neglected and historical Sicilian red-light district in Catania, Italy. This article seeks to re-signify the concept of "inclusive space" by exploring the dialectical elements and conflicts and the collaborative paths between institutions, community and third sector and aimed to spawn relational processes of co-working, co-design, and mutual learning.
plaNext-Next Generation Planning Vol. 10 (2020) : Planning inclusive spaces: An inter- and transdisciplinary approach 38-57
Keywords: collaborative practices; community-led regeneration; third sector; public space; right to the city; enabling spaces; urban marginalities